CDK 4/6 inhibitors combined with radiotherapy: A review of literature - Claire Bosacki; Wafa Bouleftour; Sandrine Sotton; Alexis Vallard; Elisabeth Daguenet; Hamza Ouaz; Iohel Cojoracu; Dariush Moslemi; Mona Molekzadehmoghani; Nicolas Magné (Clinical and Translational Radiation Oncology, 2021)
Cyclin-dependent kinase 4 and 6 inhibitors (CDK4/6i) namely palbociclib, ribociclib and abemaciclib were granted approval by the European Medicines Agency (EMA) between 2017 and 2018. They are currently prescribed in combination with hormone therapy to treat hormone receptor positive, HER2 negative metastatic or locally advanced breast cancer. Their combination with radiotherapy raises safety concerns as preclinical data enlightened their possible synergistic effect. Moreover, data about toxicity when combining CDK4/6i with radiotherapy are scarce. This review of literature focused on the use of CDK4/6i combined with radiotherapy. It aimed at listing every published data about such combination so as to understand its possible resulting toxicity in metastatic breast cancer.